Improved Performance of CLM5.0 Model in Frozen Soil Simulation Over Tibetan Plateau by Implementing the Vegetation Emissivity and Gravel Hydrothermal Schemes. Issue 6 (21st March 2023) - Luo, Jiangxin; Huang, Anning; Lyu, Shihua; Lin, Zhaohui; Gu, Chunlei; Li, Zhaoguo; Deng, Mingshan; Zhao, Wen; Liu, Wanqing
Abstract: Frozen soil is widely distributed over the Tibetan Plateau (TP) and has significant impacts on the regional climate and ecosystem. However, the Community Land Model version 5 (CLM5.0) produces evident cold bias in the frozen soil simulation over TP. In this study, an improved vegetation emissivity scheme and a gravel hydrothermal scheme have been implemented into CLM5.0 model, and their synergistic influences on the frozen soil simulation over TP have been systematically addressed and revealed. Results show that adopting the vegetation emissivity scheme, the gravel hydrothermal scheme, and both can remarkably reduce the cold bias in the frozen soil simulated by the original CLM5.0 model, and the column mean root‐mean‐square error (RMSE) can be reduced by 12.88%, 20.68%, and 31.11% at Arou site and 25.03%, 10.15%, and 36.87% at Maqu site, respectively. The reductions of column mean RMSE for the modeled soil temperature regionally averaged over TP induced by the adoption of vegetation emissivity scheme, the gravel hydrothermal scheme, and both are 32.34%, 6.75%, and 30.18%, respectively. The underlying physical mechanisms are related to the improved representation of the soil hydrothermal processes above or in the soil. The improved vegetation emissivity scheme improves the soil surface long‐wave radiation heat transfer process, while the gravel hydrothermal scheme improves the hydrothermal properties within the soil. Overall, improving the surface long‐wave radiation heat transfer and the internal soil hydrothermal properties can obviously enhance the performance of CLM5.0 model in simulating the soil freeze–thaw processes. Plain Language Summary: The frozen soil over the Tibetan Plateau (TP) exerts evident influences on regional climate and ecosystem. However, the Community Land Model version 5 (CLM5.0) produces obvious cold bias in the frozen soil simulation over the TP due to the inaccurate hydrothermal transfer processes parameterization above or within the soil. Here, we implemented the gravel hydrothermal scheme and the improved vegetation emissivity scheme into CLM5.0 to improve the model performance in simulating the frozen soil over TP. The results from the single‐point and regional simulations consistently show that the cold bias in the frozen soil simulation produced by the original CLM5.0 model can be clearly reduced by adopting the improved vegetation emissivity scheme and gravel hydrothermal scheme, indicating that accurate parameterization of hydrothermal transfer processes above or within the soil is equally important to improve the frozen soil simulation and benefits to advance our understanding of the soil freeze–thaw process. Key Points: Adopting the improved vegetation emissivity and gravel hydrothermal schemes can obviously improve the frozen soil simulations The vegetation emissivity scheme improves the soil surface long‐wave radiation heat transfer process The gravel hydrothermal scheme improves the thermal properties within the soil